Updated 1978-2001 abundance estimates and their correlations for the Bering-Chukchi-Beaufort Seas stock of bowhead whales - Zeh , Judith E.; Punt, Andre E. (J. Cetacean Res. Manage., 2023)
The method of Cooke (1996) and Punt and Butterworth (1999) for computing abundance estimates for bowhead whales of the BeringChukchi-Beaufort Seas stock is reviewed. These abundance estimates are computed from estimates N4 of the number of whales that passed within the 4km visual range of the observation ‘perch’ from which the whales are counted, the estimated proportions P4 of the whales that passed within this range and the estimated standard errors (SE) of N4 and P4. Errors discovered while assembling the data used in developing previous estimates were corrected, and new estimated detection probabilities, N4 and P4 values and SEs were computed using the corrected data. The method of Cooke (1996) and Punt and Butterworth (1999) was then applied. The resulting 2001 abundance estimate was 10,545 (95% confidence interval 8,200 to 13,500), extremely close to the 2001 N4/P4 abundance estimate of 10,470 (95% confidence interval 8,100 to 13,500) (George et al., 2004). The estimated rate of increase of this population from 1978 to 2001 was 3.4% per year (95% confidence interval 1.7% to 5%).